Endovascular management of tandem embolic stroke due to cardioembolic free-floating thrombus: a case report - Hu, Bin; Li, Jing; Li, Liang (Frontiers in Neuroscience, 2025)
BackgroundTandem lesions (TLs), defined as simultaneous occlusions of both extracranial and intracranial arteries, represent a particularly challenging subset of large vessel occlusion (LVO) strokes. While most TLs are attributed to atherosclerotic changes or arterial dissection, a smaller subset originates from cardioembolic emboli arising from the heart or aortic arch, commonly referred to as embolic tandem lesions. In rare instances, these emboli form a free-floating thrombus (FFT) in the carotid artery, characterized by mobile intraluminal thrombotic material with high embolic potential. Optimal treatment strategies for these rare and complex cases remain undefined.Case summaryWe present a rare case involving an embolic tandem lesion in a 73-year-old male with known atrial fibrillation who presented with acute ischemic stroke upon awakening. Imaging and angiography demonstrated a free-floating thrombus (FFT) at the brachiocephalic bifurcation extending into the origins of the right common carotid and right subclavian arteries, a free-floating thrombus at the carotid bifurcation, and an additional thrombus occluding the right ICA terminus and the origin of the M1 segment. A staged endovascular approach was employed: intracranial recanalization was first achieved via mechanical thrombectomy, followed by stent-assisted stabilization of the residual free-floating thrombus within the common carotid artery. The patient experienced significant neurological improvement and attained functional independence at 3-month follow-up.ConclusionThis case underscores the diagnostic and therapeutic complexity associated with embolic tandem lesions and carotid FFT involvement. Comprehensive preprocedural imaging, including assessment of the aortic arch and cervical vessels, is critical. A personalized, multi-modality endovascular approach combining thrombectomy and stenting can enable successful revascularization and favorable clinical outcomes, particularly when FFT complicates tandem occlusions.